ANALISIS PENERAPAN GLAM PADA EFEKTIVITAS LAYANAN KOLEKSI FOTO, PETA DAN LUKISAN PERPUSTAKAAN NASIONAL REPUBLIK INDONESIA - Wijaya, I Komang Dio hari; Ginting, Richard Togaranta; Suhartika, I Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2025)
This study analyzes the implementation of the Gallery Library Archive and Museum (GLAM) concept in the photo, map, and painting collection services at the National Library of Indonesia. The purpose of this research is to assess the extent to which the GLAM concept can enhance accessibility, user experience, and public understanding of the available cultural and historical collections. The research method used is qualitative with a case study approach. Data were collected through observation, interviews, and documentation.The results show that the implementation of the GLAM concept can expand accessibility and improve user experience in exploring and utilizing photo, map, and painting collections. The integration of various types of collections in a single platform provides a deeper context regarding history and culture, as well as facilitates users in accessing information. Challenges faced in implementing this concept include budget constraints and the need for adequate technological infrastructure. However, there are opportunities to enhance service effectiveness through collaboration with other institutions and the development of innovative digital platforms. In conclusion, the implementation of the GLAM concept at the National Library of Indonesia positively impacts the effectiveness of photo, map, and painting collection services and has the potential to increase information literacy and public appreciation of cultural and historical heritage.